Barvila in razbarvanje odplak: Navodila za vaje - Fakin, Darink; Ojstršek, Alenka; Gorgieva, Selestina (University of Maribor Press, 2020)
Dyes and Decolouration of Waste Water: Exercise Instructions. The presence of dyes in wastewater is unacceptable from both the aesthetic and ecological point of view. The problem of the former arises from the fact that wastewaters, which contain dyes are intensively coloured even at very low dye concentration. More problematic, compared to aesthetic problem, is the environmental impact of dyes in wastewaters. The objective risk they pose to the environment depends on the structural and physical properties of the dyes, their concentration, and the exposure in environment. The course examines the available technologies for the treatment of coloured waters, indicating that there are no simple, efficient, and affordable ways to treat complexed coloured wastewaters.